Atividades colaborativas com o geogebra: uma proposta de ensino de geometria plana - Lessa, Alessandra Mathias (2016)
Performance rates of Brazilian students have not reached favorable levels in institutional evaluations to verify mathematical learning. Even though Brazil has stood out in the global setting for its development and economic growth, like South Africa, China India and Russia — countries with these characteristics, named BRICS — it has not reached results similar to most of these countries, as in PISA, for example. Therefore, besides assessing, it is important to use the results and set goals so that this picture can be changed. This study departs from the assessment carried out in the education system in the State of Espírito Santo, Brazil: the PAEBES. The result of assessment in the year 2014 will be the basis for the methodology in this study, because it comprises indications of the skills (descriptors) which students have not yet developed. The proposal comprises challenging activities involving geometry to arouse students’ curiosity and willingness to learn in a collaborative and interesting way. Since interactivity attracts youth, the Dynamic Geometry of software GeoGebra can bridge theory to practice, allowing easier visualizations in multiple representations of the object created.